2017
DOI: 10.25100/cm.v48i3.1978
|View full text |Cite
|
Sign up to set email alerts
|

Frailty syndrome and socioeconomic and health characteristics among older adults

Abstract: Objective: To investigate the association of frailty syndrome with socioeconomic and health variables among older adults. Methods: This is a cross-sectional, observational and analytical household research conducted with a sample of 1,609 urban elderly. We used: semi-structured questionnaire, scales (Katz, Lawton and shortened version of Geriatric Depression Scale) and Fragility Phenotype proposed by Fried. Descriptive analysis was performed along with a bivariate and multinomial logistic regression model (p <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
14
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 33 publications
(135 reference statements)
5
14
1
5
Order By: Relevance
“…The finding that frailty "can occur in the absence of multimorbidity" has also been found in a study in Brazil [21]. In line with a number of studies [9,13,16,17,21], this study found an association between functional disability and frailty. This shows that our study frailty has overlap with function disability but not comorbidity.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The finding that frailty "can occur in the absence of multimorbidity" has also been found in a study in Brazil [21]. In line with a number of studies [9,13,16,17,21], this study found an association between functional disability and frailty. This shows that our study frailty has overlap with function disability but not comorbidity.…”
Section: Discussionsupporting
confidence: 88%
“…In consistence with previous studies [9,[12][13][14][15], this study found that older age, being unmarried, separated, divorced or widowed, and in the bivariate analysis that poorer economic status and lower education were associated with frailty. Frailty is associated with aging by accumulating deficiencies in several physiological systems [21].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Another explanatory variable was PIM. Initially, regular medica- Frailty syndrome-the outcome variable-was assessed considering frailty phenotype components (unintentional weight loss, decreased muscle strength, walking slowness, low physical activity levels and self-reported exhaustion and/or fatigue) (Fried et al, 2001), in agreement with previous studies (Pegorari & Tavares, 2014;Tavares, Corrêa, Dias, Ferreira, & Pegorari, 2017;Tavares et al, 2018). Based on this evaluation, subjects with three or more impairments were classified as frail, those with one or two impairments were classified as prefrail, and those with no impairments of frailty components were considered nonfrail (Fried et al, 2001).…”
Section: Data Collectionmentioning
confidence: 72%